A "special" anhydrous system for the preparation of alloyed Pd1Ce0.5 nanonetworks catalyst supported on carbon nanotubes with high electrochemical oxidation activity for formic acid. (25th May 2021) - Yang, Ping-Ping; Zhao, Peng-Cheng; Luo, Na; Li, Yu-hong; Wang, Chenxi; Zhang, Li; Xie, Yi-xi; Fei, Jun-Jie
Abstract: Herein, Pd1 Ce0.5 alloy nanonetworks (ANNs) on multi-walled carbon nanotubes (MWCNTs) supported bimetallic catalyst (referred to Pd1 Ce0.5 /MWCNTs-D) was prepared in deep eutectic solvents (DESs). The Pd1 Ce0.5 /MWCNTs-D catalyst shows remarkable catalytic performance toward formic acid oxidation (FAO) (1968.5 mA mgPd −1 ) and better CO anti-poisoning capability compare with Pd/MWCNTs-D, Pd/MWCNTs-W (prepared in water) and commercial Pd/C catalysts. The excellent network structure and synergistic effect are the main reasons for the improvement of electrochemical activity of Pd1 Ce0.5 /MWCNTs-D catalyst. This study provides a new method for preparation of high performance Pd-based electrocatalysts for direct formic acid fuel cell (DFAFC) applications. Graphical abstract: Image 1 Highlights: DESPd1 Ce0.5 alloy nanonetworks on MWCNTs catalyst was prepared in DESs. Smaller Pd1 Ce0.5 alloy nanoparticles tend to connect a nanonetworks structure. Strong charge transfer interaction is present between Pd and Ce in the catalyst. The Pd1 Ce0.5 /MWCNTs-D exhibits much higher electrocatalytic performance.